Determinação da posição de bobinas implantáveis via sistema de transferência de energia sem fio - Garcia, Lucas Ricken (2016)
This paper presents the study of a method for determining the implanted coil position and orientation relative to the transmitter coil externally located to the patient. In the electrical aspect, knowing the implanted coil position and orientation allows greater control over the placement of the link and thus the efficiency of features and power delivered to the secondary, i.e. the IMD. In the clinical aspect, detect and determine the implantable coil position, if possible, the IMD can assist in determining possible device movements in the implanted area that can influence their performance. In this sense, a theoretical analysis about the mutual inductance, the magnetic coupling coefficient and two coils wireless power transfer (WPT) systems was realized. Through mathematical model implemented in Matlab and experimental design of two coil WPT systems, the influence of lateral and angular misalignment on the magnetic coupling was assessed. From the observed characteristics, was described the necessary procedures to estimate the relative position and orientation of the implantable device coil only measuring the primary electrical parameters. In a preliminary evaluation, through virtual testing, there was an average error and standard deviation in determining the relative position of 2.4 mm and 1.1 mm, respectively, compared to the dimensions of the coils (40 mm diameter to external coil and 5.5 mm for implantable coil) indicate adequate accuracy. To the relative angle the method also yielded promising results, since the average error was 7° and the standard deviation obtained 8.2°. Thus, the method studied enables the development of equipment for determining the implanted coil relative position and orientation measuring only the primary current without the need for additional circuitry in IMD or the use of medical imaging equipment.